2012
DOI: 10.1073/pnas.1118440109
|View full text |Cite
|
Sign up to set email alerts
|

Induction of lignocellulose-degrading enzymes in Neurospora crassa by cellodextrins

Abstract: Neurospora crassa colonizes burnt grasslands in the wild and metabolizes both cellulose and hemicellulose from plant cell walls. When switched from a favored carbon source such as sucrose to cellulose, N. crassa dramatically upregulates expression and secretion of a wide variety of genes encoding lignocellulolytic enzymes. However, the means by which N. crassa and other filamentous fungi sense the presence of cellulose in the environment remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
216
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(231 citation statements)
references
References 43 publications
9
216
0
6
Order By: Relevance
“…Other than direct import of the degradation products from cellulose into cytoplasm, sensing these products may also involve a specific membrane anchored receptor (6,29,30). In the present study, a putative sugar transporter Crt1 belonging to the major facilitator superfamily was also identified.…”
Section: Discussionmentioning
confidence: 77%
“…Other than direct import of the degradation products from cellulose into cytoplasm, sensing these products may also involve a specific membrane anchored receptor (6,29,30). In the present study, a putative sugar transporter Crt1 belonging to the major facilitator superfamily was also identified.…”
Section: Discussionmentioning
confidence: 77%
“…Considering the dominance of LPMOs in the secretomes of biomass-degrading microorganisms (18), the abundance of LPMOencoding genes in such organisms, and the documented beneficial effects of LPMOs on biomass conversion, it seems that we have only seen the beginning of what may be a very important development in enzymatic biomass refining. Many important aspects of these recently discovered enzymes remain unresolved, including the catalytic mechanism and the structural determinants of substrate specificity.…”
Section: Discussionmentioning
confidence: 99%
“…and hemicellulose from the plant cell walls (Znameroski et al, 2012). In this report, we showed that the putative protein NCU09445.7 in N. crassa is actually a functional glucuronoyl esterase.…”
Section: Discussionmentioning
confidence: 72%